The scent keeper - Bauermeister, Erica (New York : St. Martin's Press, 2019)
"A moving and evocative coming-of-age novel about childhood stories, families lost and found, and how a fragrance conjures memories capable of shaping the course of our lives." -- from publisher.
Keywords: Smell -- Fiction; Families -- Fiction; Fathers and daughters -- Fiction; Bildungsromans; Magic realist fiction